Feature Extraction of Electroencephalography Signals Using Fast Fourier Transform - Hindarto, Hindarto; Sumarno, Sumarno (Bina Nusantara University, 2016)
This article discusses a method within the area of brain-computer interface. The proposed method is to use the features extracted from the Electroencephalograph signal and a three hidden-layer artificial neural network to map the brain signal features to the computer cursor movement. The evaluated features are the root mean square and the average power spectrum. The empirical evaluation using 200 records taken from 2003 BCI Competition dataset shows that the current approach can accurately classify a simple cursor movement within 92.5% accuracy in a short computation time.